A History of Burn Care - Kamolz, Lars P.; Hartmann, Bernd (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Burn injuries are still one of the most common and devastating injuries in human and the treatment of major burns remains a major challenge for physicians worldwide. Modern burn care involves many components from initial first aid, burn size and burn depth assessment, fluid resuscitation, wound care, excision and grafting/ coverage, infection control and nutritional support. Progress in each of these areas has contributed significantly to the overall enhanced survival of burn victims of the past decades. Most major advances in burn care occurred in the past 50 years, spurred on by wars and great fires. The use of systemic antibiotics and topical antiinfective agents greatly reduced sepsis related mortality. This along with the improvement of new surgical and skin grafting techniques allowed the earlier excision and coverage of deep burns which resulted in greatly improved survival rates and better functional and aesthetic outcome. In this book we look back at how the treatment of burns has evolved over the past decades and hundreds of years. The advancement of burn care has been closely associated with our deeper understanding of its pathophysiology; we have now come to understand the impact that burn injuries have in the multiple fields of current medical science i.e. in metabolism and circulation, electrolyte balance and nutrition, immunology and infection, inflammation, pulmonary function and wound healing.